Maritime Law Subject in Indonesian Law Faculty Curriculum: Supporting Indonesia’s Maritime Industry Development - I Ketut Dharma Putra Yoga; Krisnady Kesumadiksa (Media Iuris, 2022)
AbstractThis paper examines whether the inclusion of maritime law subject in the curriculum of the Indonesian faculty of law is necessary for the expansion of the maritime industry. This paper describes how education can positively influence the long-term growth of the maritime industry in Indonesia. The method used in this research is normative legal research. Basically, in accordance with the Indonesian Vision 2045, a cultural and structural maritime reformation must be implemented for the nation to become a maritime leader; one of the strategies for achieving this goal is to improve the quality of human resources through formal education with a solid curriculum. The result of this research showed that through teaching and academic research, the presence of maritime law will have a significant impact on the Indonesian maritime industry. Additionally, the presence of maritime law and research institutes will result in the reform of maritime regulations to make them more effective and business-friendly, so that the policymakers and business actors in Indonesia have strong academic partners with which to resolve maritime issues that have arisen or will arise in Indonesia through the formation of admiralty court in Indonesia.